Eﬀectiveness of rehabilitation approaches according to loss of earning capacity in Santiago de Cali, Colombia - Cantor-Barona, Gely Audrey (2020)
Objective. To determine the most eﬀective rehabilitation approach for returning to work according to the percentage of loss of earning capacity. Methods. It used a secondary information source (insurance company database named Positiva) and univariate, bivariate and Kaplan-Meier analyzes were applied to the 75 records that met the inclusion criteria. Results. They showed that there are no statistically signifcant diﬀerences between the time elapsed between "the occurrence of the event and the start of rehabilitation"; nor in between "the beginning of rehabilitation and the end of rehabilitation"; nor between “the end of rehabilitation and the discharge for return to work” in the physical, occupational and comprehensive approaches. Conclusion. This research suggests eliminating administrative delays and to legislatethat the work of rehabilitators be carried out jointly with those in charge of intervening or adapting a job position.